2012
DOI: 10.1177/0194599812462664
|View full text |Cite
|
Sign up to set email alerts
|

Adenoid Ciliostimulation in Children with Chronic Otitis Media

Abstract: At 2 and 3 hours following isoproterenol stimulation, there was a significant blunting of dynamic ciliary beat frequency in children with chronic otitis media with effusion. This ciliary dysfunction may provide a physiological explanation related to chronic adenoiditis in children with chronic otitis media.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…All patients had significantly lower ciliary activity compared to that found in normal guinea pigs. Andreoli et al found no significant difference in baseline CBF between children with AH + OSA, AH + chronic otitis media with effusion (EOM) and AH + recurrent episodes of acute otitis media (ROM). After stimulation with isoproterenol, patients with AH + EOM had significantly lower dynamic ciliary responses at 2 and 3 hours.…”
Section: Discussionmentioning
confidence: 99%
“…All patients had significantly lower ciliary activity compared to that found in normal guinea pigs. Andreoli et al found no significant difference in baseline CBF between children with AH + OSA, AH + chronic otitis media with effusion (EOM) and AH + recurrent episodes of acute otitis media (ROM). After stimulation with isoproterenol, patients with AH + EOM had significantly lower dynamic ciliary responses at 2 and 3 hours.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, tonsillectomy alone may not be a helpful treatment for otitis media because tonsils are not anatomically associated with Eustachian tube function. Biofilms of bacteria in the adenoid have been reported to cause inflammation and mucosal edema, resulting in otitis media [5,16,17]. Paradise et al suggested that otitis media could be associated with infection not only in the nasopharynx, but also in the oropharynx based on their results that T&A was narrowly more efficacious against otitis media than adenoidectomy only [1].…”
Section: Discussionmentioning
confidence: 99%